We are all believers Crisis in living conditions and the intervention of burial societies in Botswana - Ngwenya, B. Ntombi (Missionalia: Southern African Journal of Mission Studies, 2001)
Burial societies in Botswana provide financial relief to bereaved households. Over the last three decades of economic development in Botswana people have been exposed to new sources of vulnerability, including the HIV/AIDS pandemic. A burial society is a relatively autonomous, historically distinct local mutual aid institution which may be occupational or gender based, whose goal is to provide social relief and support to a member or members' family/kin experiencing distress due to death.
Free